PERANCANGAN MEDIA YOU ONLY LIVE ONCE (Y.O.L.O) SEBAGAI SARANA MENINGKATKAN MINAT BACA DAN TULIS BERBASIS WEB (STUDI KASUS FORUM LINGKAR PENA JAMBI): Reading, E-Book, You Only Live Once (YOLO), Writing - Aryanti, Dewi; -, Elzas (JURNAL AKADEMIKA, 2017)
The condition of Indonesia's own interests read community is indeedquite a concern. Low interest read can be viewed from various aspects of one community's desire to buy a conventional printed book that feels quite damning. This is where the existence of E-books began tobe felt important, practical aspects and provide a viable alternative to conventional printed books substitute relatively less expensive. Reading itself is a process of improving vocabulary, command on the language and communication skills of a person. Someone who doesn't read will always experience the rarity of words when writing and speaking. On this occasion the author doing research on Flp Jambi Region as an organization with the goal of improving the kepenulisan reading and writing culture among the public by designing a media "Media You Only Live Once (Y.O.L. O) as a means of increasing interest in read and write". Results of the study concluded that the content generated from the draft media You Only Live Once (Y.O.L. O) facilitate readers in accessing books with more easy, practical and up to date.